Shakespeare and Youth Culture - Hulbert, Jennifer; Wetmore, Kevin J.; York, Robert L.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2006)
This book explores the appropriation of Shakespeare by youth culture and the expropriation of youth culture in the manufacture and marketing of 'Shakespeare'. Considering the reduction, translation and referencing of the plays and the man, the volume examines the confluence between Shakepop and rock, rap, graphic novels, teen films and pop psychology.
Keywords: Theater; Cultural studies; Communication; Literature, Modern; Theater—History.; British literature; Theatre and Performance Studies; Cultural Studies; Media Studies; Early Modern/Renaissance Literature; Theatre History; British and Irish Literature